"Consuming" national identity in Western Ukraine. Issue 1 (2nd January 2017) - Seliverstova, Oleksandra
Abstract : This paper represents an attempt to study national identity in the post-Soviet context through the lens of everyday life practices. Building on ideas of banal nationalism and consumer citizenship, and with support of empirical evidence collected in L'viv, Ukraine, this paper demonstrates how national identity becomes materialized in everyday life through consumption practices and objects of consumption. While exploring objects and practices that are not originally national in scope but infused with national meanings by ordinary people, it will be shown how consumption becomes an arena for the expression and renegotiation of national self-portraits. Differences in national meanings among residents of L'viv belonging to two different language groups will highlight the diversity of ways and means by which people express their national sensibilities. By exploring national meanings in everyday consumption practices of Ukrainian citizens, this study aims to provide an alternative perspective on post-Soviet nation-building and contribute to the current debate on the position and identity of the Russian-speaking population of Ukraine.